Pengaruh Disiplin Kerja dan Pengawasan Langsung Terhadap Efektivitas Kerja PT. Bank Sinarmas Syariah Kcs. Sukabumi - Denisha Sundari Ekanurrahman; Erry Sunarya; Faizal Mulia Z (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study is to determine the picture of work discipline, direct supervision, and work effectiveness, to find out how much influence work discipline has on work effectiveness at PT. Bank Sinarmas Syariah Kcs. Sukabumi, and to find out how much influence direct supervision has on work effectiveness at PT. Bank Sinarmas Syariah Kcs. Sukabumi. The research method that researchers use is descriptive and associative research methods with a quantitative approach. The result of this study is the Implementation of Work Discipline in employees of PT. Bank Sinarmas Syariah Kcs. Sukabumi is already in the very high category. Direct supervision of PT. Bank Sinarmas Syariah Kcs. Sukabumi is in the very high category. Work effectiveness in employees of PT. Bank Sinarmas Syariah Kcs. Sukabumi is in the very good category. Based on the results of hypothesis testing, work discipline does not have a significant effect on the effectiveness of PT. Bank Sinarmas Syariah Kcs. Sukabumi. This is evidenced by t-count < t-table (0.295 < 2.04523). While direct supervision has a significant effect on the effectiveness of PT. Bank Sinarmas Syariah Kcs. Sukabumi. This is evidenced by t-calculate > t-table (4.606 > 2.04523).